Cricketers are not tickled pink by the new coloured ball. Issue 2 (February 2021) - Maguire, Robert; Timmis, Matthew A.; Wilkins, Luke; Mann, David L.; Beukes, Eldre; Homer, Alice; Johnstone, James A.; Adie, Joshua M.; Arnold, Derek; Allen, Peter M.
Abstract: Objectives: Cricket administrators have started scheduling long-form matches which finish at night and are played with a pink as opposed to a red ball. However, there are reports that the pink ball may introduce new dangers and alter performance. The aim of this study was to investigate professional cricketers' opinions about the visibility of the pink ball whilst playing in different lighting conditions (afternoon, dusk and night). Design: Purposeful sampling of a cross-section of elite cricketers with pink ball experiences playing in the United Kingdom. Methods: Eighty-eight international or first-class professional cricketers completed a questionnaire consisting of Likert scale and free text responses to questions covering perceptions of the pink ball, with a particular emphasis on visibility. Results: The pink ball was reported as less visible than the red ball when batting (p  <  0.001) and fielding (p  <  0.001). Within the three lighting conditions the pink ball was significantly less visible at dusk under floodlights compared to afternoon and night both when batting and fielding (ps  <  0.001). Free text comments confirmed that visibility of the pink cricket ball was most challenging at dusk (coverage 0.37), and that players sometimes experienced a blurring sensation with the pink ball leaving a visual 'trail' when viewed under floodlights (coverage 0.24). Conclusions: Results advocate that governing bodies should consider the inclusion of a break in play during dusk to enhance player safety and performance. Empirical research is needed to quantify the risks to player safety in different lighting conditions.